DIFFERENTIAL APTITUDE TEST (DAT) DALAM MENGEMBANGKAN BIMBINGAN KARIR SISWA SMA - tanjung, Noffiyanti (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
This study aims to describe the role of the Differential Aptitude Test (DAT) in enhancing career guidance services for senior high school students. Career guidance in schools is often not based on objective data regarding students’ abilities and potential, resulting in less accurate career decision-making. Therefore, the use of psychological instruments such as DAT is considered a solution to comprehensively map students’ talents, interests, and academic abilities. This research employed a library research method by analyzing various sources such as journals, books, and relevant research reports related to the implementation of DAT in career guidance. The data were analyzed using content analysis techniques to identify patterns, comparisons, and implications of DAT utilization in guidance and counseling services. The findings indicate that DAT is effective in helping guidance and counseling teachers identify students’ ability profiles in various aspects such as verbal, numerical, abstract reasoning, spatial visualization, clerical speed and accuracy, and mechanical reasoning. This information can be used to develop more personalized and targeted career guidance programs, and to assist students in selecting educational pathways or occupations aligned with their potential. In conclusion, the Differential Aptitude Test (DAT) is a relevant and significant assessment tool for strengthening career guidance implementation in senior high schools. Integrating DAT into counseling services can improve students’ career decision-making through objective, measurable, and psychology-based data